1998
DOI: 10.1210/jc.83.1.206
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Coculture Model for Benign Prostatic Hyperplasia Expressing Both Isoforms of 5 -Reductase

Abstract: We have developed a coculture system for primary fibroblast and epithelial cells derived from benign prostatic hyperplasia (BPH) that retained many of the characteristics of the intact human prostate. In contrast to separately cultured prostate fibroblast and epithelial cells, cocultures of fibroblasts and epithelial cells maintained messenger ribonucleic acid expression and functional activity for both isoenzymes of 5 alpha-reductase (type I and type II) as well as maintained expression of androgen receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Other experimental prostate models of androgen regulation of stromal-epithelial signaling [35][36][37][38] or intracrine production of DHEA metabolites (ERβ ligand 7α-hydroxy DHEA) [22] have been described. The coculture model presented herein also provides an opportunity to elucidate the role of the tumor microenvironment in cancer progression by comparing responses of epithelial cells to normal vs. reactive stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental prostate models of androgen regulation of stromal-epithelial signaling [35][36][37][38] or intracrine production of DHEA metabolites (ERβ ligand 7α-hydroxy DHEA) [22] have been described. The coculture model presented herein also provides an opportunity to elucidate the role of the tumor microenvironment in cancer progression by comparing responses of epithelial cells to normal vs. reactive stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate tissue chips were placed in ice-cold RPMI 1640 medium supplemented with 5% fetal calf serum (FCS, v/v), penicillin (100 U/ml) and streptomycin (100 mg/ml) for cell separation and culture. Prostate stromal and epithelial cells were isolated from BPH tissues and cultured as described previously (Tsugaya et al 1996, Bayne et al 1998. Stromal and epithelial cells were maintained in fibroblast growth medium (FGM) and epithelial cell growth medium (EGM) respectively.…”
Section: Prostate Tissue and Cell Culturementioning
confidence: 99%
“…5% FCS, 100 000 units penicillin and 100 mg streptomycin. Stromal and epithelial cell identities were established by phase contrast microscopy and immunocytochemical staining as described in previous reports (Tsugaya et al 1996, Bayne et al 1998. MCF-7 human mammary adenocarcinoma cells were obtained from ATCC (Teddington, UK) and maintained in minimal essential medium supplemented with 5% FCS.…”
Section: Prostate Tissue and Cell Culturementioning
confidence: 99%
“…We failed to observe secretory function in these spheroids, with no expression of PSA or PAP, but this may be due to a requirement for further stromal-cell-derived signals that are not present in the conditioned medium. The importance of stromal/epithelial interactions in normal prostate growth and differentiation has been demonstrated both in vivo 46 and in vitro 47 and Collins et al 48 showed that a stem-cell-enriched population of cells could produce three-dimensional structures with basal cells and fully secretory differentiated luminal cells, when engrafted into athymic male mice in the presence of human stromal cells. More recently, Lang et al 49 showed that differentiation in Matrigel could be further improved by the addition of serum and oestrogen.…”
Section: Stem-cell Pluripotencymentioning
confidence: 99%